Kinetic Studies on an Algal Biofilm Reactor for Raw Sewage Water Treatment. Issue 9 (16th August 2016) - Gera, Gayatri S.; Yewalkar, Swati N.; Nene, Sanjay; Kulkarni, Bhaskar D.; Kamble, Sanjay
Abstract: A packed‐bed algae biofilm reactor was developed using porous and nonporous dual packings. The biofilm was cultivated on reticulated polyurethane foam cubes. The nonporous glass Raschig rings were taken as bed support that helps to remove generated gas from the system. The effect of variables such as column length‐to‐diameter ratio, catalyst cube dimension, and feed flow rate on the treatment of sewage water was studied. The reaction kinetics indicates that the nutrients uptake rate is dependent on both pore and film diffusion. The kinetics of uptake of nutrients follows a pseudo first‐order reaction. From the pseudo reaction rate constant, Thiele modulus and effectiveness factor were calculated and a kinetic model equation for fractional nutrient uptake was developed in terms of operating variables. The model can predict the reaction rate with low deviation. The results obtained may be valuable for large‐scale treatment of sewage water. Abstract : The application of cheap, reusable, inert, autoclavable matrices with high porosity as support for biofilm‐based sewage treatment in packed‐bed algal biofilm reactors is proposed. A kinetic multivariable regression model predicts nutrient uptake efficiency and will help in scaling‐up of this algal biofilm reactor to design strategies for large‐scale treatment of sewage water.